2002
DOI: 10.1590/s0104-66322002000200012
|View full text |Cite
|
Sign up to set email alerts
|

Use of tower reactors for continuous ethanol production

Abstract: -The purpose of this work was to develop a continuous fermentation system operating with a tower reactor using some flocculent yeast strains isolated from an industrial process. The strain was an used in the trial of the proposed system, composed of two serial glass tower reactor. The effects of the following variables were studied on the yield and productivity of the system: total reducing sugar (TRS), concentration in feeding, recycle flow in the second reactor, residence time and diameter/height ratio of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Viegas [14] reported a yield of approximately 87 % in a conventional continuous fermentation unit using a centrifugal separator and non-flocculating yeast in mixing reactors with molasses as the feedstock. Viegas et al [17] achieved a yield of 93 % operating continuously with two tower reactors connected in series, a cell recirculation system, and yeast flocculation. According to Paiva et al [28], a tower fluidized reactor with recycle and cell separation by sedimentation produced a yield of 88.3 %.…”
Section: Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Viegas [14] reported a yield of approximately 87 % in a conventional continuous fermentation unit using a centrifugal separator and non-flocculating yeast in mixing reactors with molasses as the feedstock. Viegas et al [17] achieved a yield of 93 % operating continuously with two tower reactors connected in series, a cell recirculation system, and yeast flocculation. According to Paiva et al [28], a tower fluidized reactor with recycle and cell separation by sedimentation produced a yield of 88.3 %.…”
Section: Yieldmentioning
confidence: 99%
“…When operating with flocculent yeast in a continuous system with cell recircula- tion, the fluidized-bed reactor produced a substrate conversion greater than 95 % [17]. A substrate conversion of 98 % was obtained with different substrate concentrations ranging from 125 to 181 g L -1 in a continuous fermentation system with cell recycle in two tower reactors [14].…”
Section: Residual Sucrose Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…These strains appear to be superior to those immobilized via support; they are retained in the reactor when forming flocs of appropriate size, without problems of cell growth, and can be recovered by a sedimentation process, thus eliminating the use of centrifuges [1,2]. Different reactor configurations have been tested to achieve fermentation using these strains, including air lift reactors, single-tower reactors, or two tower reactors connected in series [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…) (Da-Costa et al, 1997;Baptisa-Neto et al, 2005). Therefore, continuous culture systems have been widely used to cultivate microbes for industrial and research purposes (Zangirolami et al, 2002;Viegas et al, 2002;Kim et al, 2004;Neto et al, 2005;Dominguez et al, 2009). Few studies have been reported on the continuous production of xylanases with bacteria and fungi, mainly because of the problems associated with media containing insoluble xylan substrates (Tangnu et al, 1981;Rőthlisberger et al, 1992).…”
Section: Introductionmentioning
confidence: 99%